L’œuvre d’Alan Berliner ou l’autobiographie comme l’affaire de tous - Jean-Luc Lioult (Revue LISA)
Alan Berliner is a fascinating, unclassifiable independent filmmaker who has devoted 25 years to the making of films which have led him from a reflection on family in general to the questioning of his own family, then to an interrogation on identity and finally to his self-portrayal as an artist. These works do not completely meet the usual standards of subjective or autobiographical documentaries. Historically speaking, Berliner may appear as an inheritor of various trends dealing with intimacy and self-inscription. According to the criteria formulated by Bill Nichols, his works display a strong reflexivity, and subsequently a good deal of performativity. But above all, he has developed a style of his own. He is a virtuoso of montage creating sophisticated signifying figures, often dissociating the sound from the image, to reveal latent meanings, unexpected correspondences, contradictions and distortions. Nobody’s Business, possibly his masterpiece, draws a portrait of his own (reluctant) father and shuffles around History, individual life storytelling, psychodrama and genetics, to eventually convince us that the personal is universal.